Quarantine and its Impact on the Environment - Hussein, Zahraa Ahmad; Shehab, Marwa Abdelsattar; Abdulkader, Abdulkader Salam (Journal of Ecohumanism, 2024)
Quarantine is a common public health strategy used to help prevent the spread of highly contagious diseases. According to the Centers for Disease Control and Prevention, quarantine is a preventive measure that separates and restricts the movement of people who have been exposed to an infectious disease to find out whether they are sick or not. Some positive phenomena have been observed on the environment, varying from place to place. There has been an increase in air quality, and the satellites have recorded a significant decline in toxic gas emissions. The positive impact has been extended to include water. In addition, noise has been reduced due to the disruption of the movement of trains, buses and cars. Other positive effects included clarifying the importance of a healthy lifestyle such as exercises, healthy food, staying away from smoking and paying attention to cleanliness, all of which are effective factors in reducing the spread of the epidemic, in addition to promoting a sense of responsibility towards society, dealing positively with crises, flexibility in changing the routine of life and leisure time, learning to refrain from things that people used to and disappeared with the current situation, in addition to contributing to the return of the spirit of humanitarian cooperation and teamwork.